Case report: From oral infection to life-threatening pneumonia: clinical considerations in Nocardia infection from a case - Chen, Kang; Wang, Ying; Dong, Jing; Wu, Ping-Shang; Yang, Jun; Ai, Guo-Ping (Frontiers in Medicine, 2024)
Nocardia is an anthropozoonotic bacteria that occurs widely in the natural environment. However, because it is a gram-positive aerobic opportunistic pathogen, it rarely occurs in patients with no prior history of immune function disease. Since the symptoms are nonspecific the diagnosis of Nocardia pneumonia is challenging. Previous studies have not reported that this anthropozoonotic bacteria colonizing the human body could cause severe pneumonia by gingival pain and pharyngeal discomfort. This case report describes a previously healthy 60-year-old female farmer who presented to the doctor with gingival pain and pharyngeal discomfort. She was treated with a dental cleaning and oral metronidazole. The patient rapidly progressed to breathing difficulties. Lung shadow was found by computerized tomography examination. The radiologist diagnosed pulmonary tuberculosis as image-based. Through laboratory examination and culture of pathogenic microorganisms in the sputum and blood of the patient, no obvious positive findings were found. The disease progressed rapidly to tracheal intubation ventilator assisted breathing. Subsequently, the patient underwent alveolar lavatory examination under endotracheal intubation fiberbronchoscopy, and the culture of alveolar lavage fluid indicated Nocardia.According to this result, the patient's disease was quickly controlled after selecting the targeted drug compound sulfamethoxazole and intravenous meropenem for treatment. In view of the reason for the high misdiagnosis rate due to the low positive rate of Nocardia culture in most cases, the clinical thinking of diagnosis and treatment from oral infection symptoms to fatal pneumonia reported in this case has certain clinical popularization and enlighten significance, not only improved the diagnosis and treatment of rare diseases, but also be reduced medical disputes.